Accessing alpha-arylated nitriles via BF3 center dot OEt2 catalyzed cyanation of para-quinone methides using tert-butyl isocyanide as a cyanide source - Shirsath, Sachin R.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (Journal of Organic Chemistry, 2018)
BF3 center dot OEt2 catalyzed 1,6-conjugate addition of tertbutyl isocyanide to para-quinone methides and fuchsones for the synthesis of alpha-diaryl and alpha-triaryl nitriles has been reported. This protocol allows alpha-diaryl- and alpha-triaryl nitriles to be accessed in good to excellent yields and with a broad substrate scope, which could be further functionalized to give a versatile set of products. This is the first example wherein tert-butyl isocyanide has been used as a cyanide source for the 1,6-conjugate addition.

Identification of potent chromone embedded [1,2,3]-triazoles as novel anti-tubercular agents - Nalla, Viswanadh; Shaikh, Aslam; Bapat, Sanket; Vyas, Renu; Karthikeyan, M.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, M. (Royal Society Open Science, 2018)
A series of 20 novel chromone embedded [1,2,3]-triazoles derivatives were synthesized via an easy and convenient synthetic procedure starting from 2-hydroxy acetophenone. The in vitro anti-mycobacterial evaluation studies carried out in this work reveal that seven compounds exhibit significant inhibition against Mycobacterium tuberculosis H37Rv strain with MIC in the range of 1.56-12.5 mu g ml(-1). Noticeably, compound 6s was the most potent compound in vitro with a MIC value of 1.56 mu g ml(-1). Molecular docking and chemoinformatics studies revealed that compound 6s displayed drug-like properties against the enoyl-acyl carrier protein reductase of M. tuberculosis further establishing its potential as a potent inhibitor.

Transition metal free regio-selective C–H hydroxylation of chromanones towards the synthesis of hydroxyl-chromanones using PhI(OAc)2 as the oxidant - Viswanadh, N. (Chemical Communications, 2018)
The chromanone scaffold is considered as a privileged structure in drug discovery. Herein, we report a highly efficient PhI(OAc)2 mediated regioselective, direct C–H hydroxylation of chromanones. This method offers easy access to substituted 6-hydroxy chromanones in moderate to good isolated yields, thus paving the way for their pharmaceutical studies.

Alternative synthesis of the CNS stimulant Prolintane - Mujahid, M.; Korpe, G. V.; Deshmukh, S. P.; Bhadange, S. G.; Muthukrishnan, M. (Arkivoc, 2019)
An alternative synthesis of prolintane, a CNS stimulant, is reported using commercially available allyl benzene in good overall yield (32.3%). The key transformations include epoxidation, Grignard reaction, Mitsunobu and reduction protocols.

Efficient and cost effective synthesis of acetamides catalyzed by calcium chloride - Sangole, M. T.; Thorat, S. M.; Shirsath, S.; Deshmukh, S. P.; Muthukrishnan, M.; Mujahid, M. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
CaCl2 has been found to be an efficient and cost effective catalyst for the rapid synthesis of acetamides in high yields. The use of stoichiometric quantities of acetic anhydride under solvent free conditions without any additional chromatographic purifications makes this protocol a safe alternative to the existing methods.
Keywords: Acetamide; acetylation; Acylation; Amine; CaCl2

Efficient synthesis of optically active neolignans ligraminol D and E - Ghotekar, Ganesh S.; Mujahid, M.; Muthukrishnan, M. (Synthesis-Stuttgart, 2019)
Efficient syntheses of optically active neolignans ligraminol D and E were achieved in four simple steps starting from easily available chiral benzyl glycidyl ethers. The products were obtained in good overall yields and high enantioselectivities. The protocol might also be useful in the synthesis of other ligraminols or related neolignans.
Keywords: benzyl glycidyl ether; Epoxide; lignan; ligraminol; Mitsunobu

New enantioselective synthesis of antiobesity drug lorcaserin - Ghotekar, Ganesh S.; More, Devidas A.; Nalla, Viswanadh; Muthukrishnan, M. (New Journal of Chemistry, 2019)
A simple and efficient enantioselective synthesis of anti-obesity drug lorcaerin starting from easily accessible 3-chlorostyrene oxide has been described for the first time employing hydrolytic kinetic resolution as a source of chirality. The protocol might also be useful in the synthesis of structural variants of lorcaserin.

Oxone promoted dehydrogenative Povarov cyclization of N-aryl glycine derivatives: an approach towards quinoline fused lactones and lactams - More, Devidas A.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (RSC Advances, 2019)
Oxone promoted intramolecular dehydrogenative imino Diels-Alder reaction (Povarov cyclization) of alkyne tethered N-aryl glycine esters and amides has been explored, thus affording biologically significant quinoline fused lactones and lactams. The reaction is simple, scalable, and high yielding (up to 88%). The method was further extended to prepare biologically important luotonin-A analogues and the quinoline core of uncialamycin.

Synthesis, biological evaluation and molecular modeling studies of novel chromone/Aza-chromone fused α-aminophosphonates as Src kinase inhibitors - Bapat, Sanket; Viswanadh, N.; Mujahid, M.; Shirazi, Amir Nasrolahi; Tiwari, Rakesh; Parang, Keykavous; Karthikeyan, Muthukumarasamy; Muthukrishnan, M.; Vyas, Renu (Journal of Scientific and Industrial Research, 2019)
A series of novel chromone/aza-chromone fused α-aminophosphonate derivatives were synthesized in good yields using silica chloride as the catalyst. All the synthesized compounds were tested for their c-Src kinase inhibitory activity. Aza-chromone compound showed Src kinase inhibition with an IC50 value of 15.8 µM. The compounds were subjected to molecular docking and dynamics simulations to study the atomic level interactions with an unphosphorylated proto-oncogenic tyrosine protein kinase Src (PDB code 1Y57) as well as phosphorylated tyrosine protein kinase Src (PDB code 2H8H). Docking and molecular dynamic results revealed phosphorylated Src tyrosine kinase protein better results than unphosphorylated tyrosine Src kinase protein. Chemoinformatics study revealed the compounds had lead like properties. Machine learning (SVR) models were built to study the structure activity correlations. A CC of 0.835 was obtained when the SVR model was applied to the 17 synthesized compounds. It is envisaged that the work will provide guidelines for future drug design efforts for Src kinase inhibitors.

Synthesis, biological evaluation and molecular modeling studies of novel chromone/Aza-Chromone fused alpha-aminophosphonates as src kinase inhibitors - Bapat, S.; Viswanadh, N.; Mujahid, M.; Shirazi, A. N.; Tiwari, R. K.; Parang, K.; Karthikeyan, M.; Muthukrishnan, M.; Vyas, Renu (Journal of Scientific & Industrial Research, 2019)
A series of novel chromone/aza-chromone fused alpha-aminophosphonate derivatives were synthesized in good yields using silica chloride as the catalyst. All the synthesized compounds were tested for their c-Src kinase inhibitory activity. Aza-chromone compound showed Src kinase inhibition with an IC50 value of 15.8 mu M. The compounds were subjected to molecular docking and dynamics simulations to study the atomic level interactions with an unphosphorylated proto-oncogenic tyrosine protein kinase Src (PDB code 1Y57) as well as phosphorylated tyrosine protein kinase Src (PDB code 2H8H). Docking and molecular dynamic results revealed phosphorylated Src tyrosine kinase protein better results than unphosphorylated tyrosine Src kinase protein. Chemoinformatics study revealed the compounds had lead like properties. Machine learning (SVR) models were built to study the structure activity correlations. A CC of 0.835 was obtained when the SVR model was applied to the 17 synthesized compounds. It is envisaged that the work will provide guidelines for future drug design efforts for Src kinase inhibitors.

Total synthesis of marine natural products serinolamide A and columbamide D - Ghotekar, G. S.; Mujahid, M.; Muthukrishnan, M. (ACS Omega, 2019)
In this report, an expeditious synthesis of two new biologically active marine natural products serinolamide A and columbamide D is documented. This convergent approach involves the key steps such as hydrolytic kinetic resolution, cross metathesis, Grignard reaction, Johnson–Claisen rearrangement, Mitsunobu, and so forth. Both of the target molecules were obtained from a common precursor (R)-7 with high enantioselectivity, less synthetic steps, and in good overall yields (serinolamide A 66% and columbamide D 62%).

Transition-metal-free benzannulation of tricarbonyl derivatives with arynes: access to 1,3-dinaphthol precursors for the synthesis of rhodamine dye analogues - Ghotekar, Ganesh S.; Shaikh, Aslam C.; Muthukrishnan, M. (Journal of Organic Chemistry, 2019)
Herein, we report a transition-metal-free annulation reaction of benzynes and 1,3-oxopentanedioate for the synthesis of highly functionalized naphthalene derivatives for the first time. Additionally, the representative naphthalene derivatives have been successfully transformed into the new series of rhodamine dye analogues.

1,6-Conjugate addition initiated formal [4+2] annulation of p-quinone methides with sulfonyl allenols: a unique access to spiro[5.5]undeca-1,4-dien-3-one scaffolds - Ghotekar, Ganesh S.; Shirsath, Sachin R.; Shaikh, Aslam C.; Muthukrishnan, M. (Chemical Communications, 2020)
An expedient one-pot synthesis of carbocyclic spiro[5.5]undeca-1,4-dien-3-ones via 1,6-conjugate addition initiated formal [4+2] annulation sequences by employing p-quinone methides and sulfonyl allenols is presented. Furthermore, this synthetic protocol tolerates a wide variety of p-quinone methides and sulfonyl allenols and affords the corresponding structurally unique spiro[5.5]undeca-1,4-dien-3-ones in good yield under mild reaction conditions.

Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

Iron catalyzed tandem ring opening/1,6-conjugate addition of cyclopropanols with p-quinone methides: new access to gamma,gamma-diaryl ketones - Shirsath, Sachin R.; Chandgude, Sagar M.; Muthukrishnan, M. (Chemical Communications, 2021)
An iron(iii) catalyzed tandem ring opening/1,6-conjugate addition of cyclopropanols to p-quinone methides leading to gamma,gamma-diaryl ketones has been described. This catalytic protocol provides a novel and efficient method to access gamma,gamma-diaryl ketone derivatives in good to excellent yields with high functional group tolerance. Importantly, gamma,gamma-diaryl ketone can be further functionalized to give a versatile set of useful products.

Metal- and light-free direct C-3 ketoalkylation of quinoxalin-2(1H)-ones with cyclopropanols in aqueous medium - More, Devidas A.; Mujahid, M.; Muthukrishnan, M. (ChemistrySelect, 2022)
Direct oxidative C-3 ketoalkylation of quinoxalin-2(1H)-ones with cyclopropanols using ammonium persulfate in an aqueous medium has been achieved in a moderate to good yield. The reaction does not require metals, light-source, or catalysts to facilitate the reaction and could be efficiently utilized to construct a wide range of biologically relevant 3-ketoalkylated quinoxalin-2(1H)-ones.
Keywords: aqueous medium; cyclopropanols; ketoalkylation; metal-free; quinoxalin-2(1H)-ones

Metal-free aminocarbonylation of p-quinone methides with isocyanides: synthesis of sterically hindered alpha-arylated acetamides - Shirsath, Sachin R.; More, Devidas A.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2022)
The synthesis of sterically hindered alpha-arylated acetamides generally requires a multistep reaction sequence and is also difficult to access due to steric constraints. This protocol allows the synthesis of sterically hindered alpha-arylated acetamides in moderate to high yields via 1,6-addition of isocyanides to p-quinone methides in the presence of BF3 center dot OEt2. The present transformation features transition metal-free conditions, avoiding the use of toxic carbon monoxide, broad substrate scope, mild reaction conditions, and operational simplicity.
Keywords: Aminocarbonylation; Isocyanide; p-Quinone methide; Sterically Hindered alpha-Arylated Acetamides

Thallium(III) p-tosylate (TTS) mediated oxidative rearrangement of 2-naphthyl and 2-heteroarylchromanones - Kurapati, Chidvilas; Muthukrishnan, M.; Singh, V. Om; Gundla, Rambabu (Indian Journal of Chemistry, 2022)
A practical and effective approach towards the synthesis of 3-hetroaryl-4H-chromen-4-ones by the oxidative rearrangement of the respective 2-hetroaryl chroman-4-ones using thallium(III) p-tosylate is described. The oxidative rearrangement of alpha and beta-naphthyl and thiophene behave like aryl groups. However, pyridyl groups give only the dehydrogenated product.
Keywords: 2-(3-pyridyl)chromones; 2-(4-pyridyl)chromones; 2-and 3-(2-theinyl)chromones; 2-and 3-(3-theinyl)chromones; 2-and 3-(?-naphthyl) chromones; Dehydrogenation; Oxidative rearrangements; thallium(III) acetate; thallium(III) p-tosylate

BF3.Et2O-catalyzed selective C-4 alkylation of isoquinolin1(2H)-ones employing p-quinone methides - More, Devidas A.; Ghotekar, Ganesh S.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2023)
The direct C-4 alkylation of isoquinolin-1(2H)-one moiety is a challenging transformation in organic synthesis. Here we present a practical and efficient synthesis of C-4 alkylated isoquinolin-1(2H)-ones through conjugate addition of isoquinolin-1(2H)-ones to p-quinone methides for the first time. The process is facilitated by Lewis acid catalysis and this operationally straightforward, mild, metal-free and one-pot transformation provides a wide range of C-4 alkylated isoquinolin-1(2H)ones at ambient temperature in good to excellent yields.

Metal- and photocatalyst-free, visible-light-initiated C3 a-aminomethylation of quinoxalin-2(1H)-ones via electron donor-acceptor complexes - More, Devidas A.; Shirsath, Sachin R.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
We report a metal- and photocatalyst-free C3 a-aminomethylation of quinoxalin-2(1H)-ones with N-alkyl-N-methylanilines. The reaction proceeds through the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-ones and N-alkyl-N-methylanilines. The present method provides a mild and environmentally friendly protocol that exhibits good atom economy and excellent functional group tolerance to obtain a library of biologically significant C3 a-aminomethylated quinoxalin-2(1H)-ones in good yields.

Palladium-catalyzed oxidative cyclization of ?-allenols in the presence of TBN: access to 3(2H)-furanones - Ghotekar, Ganesh S.; Shinde, Ravi A.; Saswade, Sagar S.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
A new palladium-catalyzed oxidative cyclization of alpha-allenols is described. The readily accessible alpha-allenols participate in intra-molecular oxidative cyclization in the presence of TBN to grant access to multisubstituted 3(2H)-furanones, which are common motifs in several biologically important natural products and pharmaceuticals.
Keywords: Alternatively; conditions; cumbersome workup; intramolecular electrophilic; multiple reaction steps; noted examples

Cu-catalyzed multicomponent reaction of arylhydrazines with β-ketoesters and TBN: one-pot access to N 2-aryl 1,2,3-triazole-1-oxides - Mujahid, Mohammad; Vara, Vijay; Arshad, Usman; Gamidi, Rama Krishna; Muthukrishnan, M. (Journal of Organic Chemistry, 2024)
We report a copper-catalyzed one-pot, multicomponent strategy for the convenient synthesis of N 2-aryl 1,2,3-triazole-1-oxides using arylhydrazines, beta-ketoesters, and tert-butyl nitrite. This mild and simple reaction proceeds in an atom-economic manner with broad substrate scope, affording a variety of N 2-aryl 1,2,3-triazole-1-oxide derivatives. Other salient features of the reaction are good functional group tolerance, scalability, and product diversification.

Visible-light mediated C-3 amination of quinoxalin-2(1H)-ones via electron donor-acceptor complexation - More, Devidas A.; Gayathri, P. R.; Thete, Kishor R.; Muthukrishnan, M. (Asian Journal of Organic Chemistry, 2024)
The formation of carbon-nitrogen bonds holds paramount importance in the realm of synthetic organic chemistry, finding extensive applications in the synthesis of pharmaceuticals, agrochemicals, and organic materials. Herein, we describe a novel EDA complex mediated, metal- and photocatalyst-free, visible-light-initiated direct C-3 amination of biologically important, quinoxalin-2(1H)-one moiety. The key to the success lies in the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-one and amine, which undergo subsequent electron transfer reaction to effect the desired transformation. A diverse array of 3-aminoquinoxalin-2(1H)-ones were prepared employing this process and the yields are up to 87%. This work represents a significant advancement toward a more environmentally friendly and efficient approach, characterized by mild reaction conditions and a high atom economy.
Keywords: C-3 amination; Dehydrogenative amination; EDA complex; quinoxalin-2(1H)-ones

Ag(I)-catalyzed heterocyclization/[3+2] cycloaddition of α-alkynylenones with β-enaminones: tandem access to highly substituted cyclopenta[c]furans - Vara, Vijay; Thete, Kishor R.; Panikar, Sera Deepu; Khan, Akram A.; Muthukrishnan, M. (Journal of Organic Chemistry, 2025)
A robust Ag(I)-catalyzed tandem heterocyclization/[3 + 2] cycloaddition of alpha-alkynylenones with beta-enaminones was developed, enabling efficient synthesis of cyclopenta[c]furans with good yields, operational simplicity, and broad substrate scope. In addition, it also presents an extended methodology to synthesize unsymmetrical tri(hetero)aryl methane having chromone and furan/pyrrole scaffolds by a slight modification of starting materials. Moreover, the synthesized cyclopenta[c]furans exhibit good fluorescence properties with quantum yields ranging from 0.33 to 0.53, as suggested by the photophysical studies.

Efficient Copper-Catalyzed, One-Pot Synthesis of N2-Aryl Phosphoryl 1,2,3-Triazole 1-Oxides - Mujahid, M.; Bhavar, Akshay A.; Vara, Vijay; Gonnade, Rajesh; Muthukrishnan, M. (Asian Journal of Organic Chemistry, 2025)
A simple and facile one-pot process has been developed for the synthesis of N 2-aryl phosphoryl 1,2,3-triazole 1-oxide derivatives. This new approach utilizes simple and commercially available starting materials, operating under mild conditions. The method employs copper-catalyzed multicomponent reaction, involving the combination of arylhydrazines, beta-ketophosphonates, and tert-butyl nitrite. The developed protocol shows excellent functional group tolerance permitting an extensive range of substrate scope up to 92% isolated yield.
Keywords: Copper-catalyzed; Phosphoryl triazoles N-oxides; Phosphorylated compound; Triazole N-oxides

Iron mediated oxidative ring opening-homocoupling of cyclopropanols: facile access to 1,6-diketones - Shinde, Ravi A.; Shirsath, Sachin; Muthukrishnan, M. (ChemistrySelect, 2025)
We have developed a new approach for the synthesis of 1,6-diketones via iron-catalyzed ring opening of cyclopropanol with a nontoxic, inexpensive iron catalyst under open-air conditions. This method eliminates the need for additives and employs tert-butanol as an eco-friendly solvent. This methodology allows rapid access to a variety of symmetrical 1,6-diketones under mild conditions. Preliminary mechanistic studies revealed the involvement of radical pathways.
Keywords: 1; 6-Diketone synthesis; C & horbar; C bond cleavage; cyclopropanols; Homocoupling; Iron mediated

Manganese-mediated cascade radical oxidative cyclization/1,6-conjugate addition of unsaturated oximes with p-quinone methides: facile access to β,β-diarylmethine substituted isoxazolines - Vara, Vijay; Thete, Kishor R.; Ghotekar, Ganesh S.; Muthukrishnan, M. (Chemistry-An Asian Journal, 2025)
A simple and efficient strategy for the synthesis of structurally diverse beta,beta-diarylmethine substituted isoxazoline derivatives have been developed. This approach employs a manganese-promoted oxidative cyclization coupled with a 1,6-conjugate addition of unsaturated oximes to p-quinone methides. The key features of this study include the formation of C-O and C-C bonds through intramolecular and intermolecular interactions, facilitated by in situ generated iminoxyl radicals. beta,beta-diarylmethine substituted isoxazolines, bearing a wide range of functional groups, were isolated in high yields.
Keywords: p-Quinone methide; diarylmethine substituted isoxazolines; Iminoxy radical; Manganese catalyzed

Phosphine-catalyzed nucleophilic ring opening of cyclopropenones with sulfoximines to access N-α,β-unsaturated acyl sulfoximines - Thete, Kishor R.; Vara, Vijay; Khan, Akram A.; Muthukrishnan, M. (Journal of Organic Chemistry, 2025)
Herein, we describe the formation of biologically relevant N-alpha,beta-unsaturated acyl sulfoximines via phosphine-catalyzed C-C bond activation of cyclopropenones with weakly nucleophilic sulfoximines. The new process does not require a transition metal or external oxidant and displays high regioselectivity and exclusive E-selectivity. Other salient features of the method are a broad substrate scope, high compatibility with various functional groups, and high atom economy.

Copper-catalyzed radical 1,2-oxysulfoximination of β,γ-unsaturated oximes for the synthesis of sulfoximine-substituted isoxazolines - Thete, Kishor R.; Vara, Vijay; Patel, Raj Y.; Muthukrishnan, M. (Organic & Biomolecular Chemistry, 2026)
Herein, we report a copper-catalyzed radical 1,2-oxysulfoximination of beta,gamma-unsaturated oximes. The transformation proceeds via intramolecular iminoxyl radical cyclization followed by interception with sulfoximines, enabling efficient access to sulfoximine-substituted isoxazolines in good yields under mild, oxidant-free conditions. The protocol operates at ambient temperature, exhibits a broad substrate scope with excellent functional group tolerance, and is readily scalable to gram quantities.

Radical-promoted cyclization of 3-allyl-2-arylquinazolinones mediated by silver(i) salts to access SCF3/SCN-enriched dihydroisoquinolino[1,2-b]quinazolinones - Vara, Vijay; Thete, Kishor R.; Khan, Akram A.; Muthukrishnan, M. (Organic & Biomolecular Chemistry, 2026)
Herein, we describe an efficient approach for the synthesis of SCF3- and SCN-functionalized polycyclic dihydroisoquinolino[1,2-b]quinazolinones through radical-mediated thio-functionalization of allylic alkenes followed by intramolecular cyclization. The transformation proceeds through sulfur-radical-triggered C-S and C-C bond formation, providing an efficient route to sulfur- and fluorine-enriched polycyclic quinazolinones. Moreover, this strategy offers high atom economy, operational simplicity, and broad substrate compatibility.